Medical (doctor’s) error: concept and causes of its occurrence - K. O. Skrynnikova (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The concept of “medical (doctor’s) error” is analysed from the doctrinal standpoint. The existing approaches (legal and medical) to defining the legal nature of a medical (doctor’s) error have been considered. It has been argued that this topic is of great theoretical and practical importance, since errors and negligence of doctors and medical staff can cause irreparable harm to patients' health or lead to death. The problem is complex, because it requires both medical and legal knowledge, and is related to the most important and difficult issue of qualifying certain acts. It has been concluded that the term “medical (doctor’s) error” is the most appropriate one, but it is absent in Ukrainian legislation. It has been proposed to introduce appropriate amendments to the legislation in the field of medicine and to enshrine the concept of “medical (doctor’s) error”, types and causes of its occurrence legally. The main characteristics of the category of medical (doctor's) error have been substantiated, and its content has been defined.